Pelatihan Penggunaan Platform Desain Grafis dan Konten Publikasi dengan Aplikasi Canva sebagai Media Penunjang dalam Meningkatkan Penjualan pada Siswa Kejuruan Kuliner - Fakhriani Ekawati; Lilis Anggraini; Muharir Muharir (Jurnal Pelayanan Hubungan Masyarakat, 2023)
At every vocational school in Indonesia it aims to prepare students to work in a particular field. One of it is a culinary expertise program where students are required to have good knowledge and skills in preparing, cooking and serving ready-to-eat food as well as being entrepreneurial and competitive in working world. To support student skills so that later they can help produce graduates who are ready to work independently in the culinary field in terms of product marketing, it requires graphic design and content training publication. Training on the use of graphic design platforms and publication content with the Canva application as a supporting medium in increasing sales to students Culinary Vocational is one of the skills needed by students culinary vocational school at SMK Negeri 4 Banjarmasin to grow the soul the entrepreneurs. One of the best Graphic Design and Content Publication Platforms accessible for free and easy to use is the Canva App. So that this training can be received and used by students later, good while still in school or when graduating from school, then for the method training in community service is to utilize the module that directly made using the Canva application and direct practice using Canva via Android or PC that can be used. At this training accompanied by three community service team members and two members from student. It is hoped that there will be training in the use of graphic design platforms and the content of this publication can improve skills and grow the soul entrepreneur students so that they can always compete in the world of work later.